Niger : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper Progress Report. (IMF Staff Country Reports; Country Report ;, 2005)
This Joint Staff Advisory Note reviews the Poverty Reduction Strategy Paper Progress Report for Niger. The lackluster economic performance in 2004 underscores Niger's vulnerability to exogenous shocks. The progress report suggests that to firmly put the economy on a path of sustained and strong growth, reforms to improve the supply response should be expedited. The report also stresses that the implementation of recently developed growth-enhancing strategies, especially for the rural and infrastructure sectors, should be expedited; and complementary strategies such as for export diversification and tourism development should be defined.